(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2019)
The objective of the present paper is to observe whether the Bolsa Familia Program (PBF), a Brazilian conditioned cash transfer program, had influence on GDP of the municipalities of the state of Sergipe during the years 2004-2012. Its innovative feature lies in the investigation of the macroeconomic impacts of PBF in the state of Sergipe. In this sense, the work is structured in four sections, besides the introduction: in the first one the origins, the design and the PBF macroeconomic as well as consumption impacts are presented. The second section briefly describes the focused region: the state of Sergipe, which is the smallest Brazilian state, meanwhile the third section presents the data and methodology employed as well as analyses the results of the experiment which does not prove the PBF influence on GDP of the investigated municipalities. Finally, the main conclusions are summarized.